The system of environmental education and upbringing at school - Kiseliova M. M. (Science, education, society: trends and prospects, 2024)
In the modern era, issues of interaction between nature and society have become extremely complex, and one of the directions of the teacher's work is to increase the environmental literacy of students, arm them with skills in the careful use of natural resources, and form an active humane position towards nature.
Keywords: экологические акции; экологизация учебного предмета; исследовательская и проектная деятельность; образовательные события; environmental actions; greening of the educational subject; research and project activities; educational events